2019
DOI: 10.1002/adma.201901361
|View full text |Cite
|
Sign up to set email alerts
|

Finite Size Effects on the Switching Dynamics of Spin‐Crossover Thin Films Photoexcited by a Femtosecond Laser Pulse

Abstract: Using ultrafast optical absorption spectroscopy, we have studied the room-temperature spinstate switching dynamics induced by a femtosecond laser pulse in high-quality thin films of the molecular spin-crossover complex [Fe(HB(tz)3)2] (tz = 1,2,4-triazol-1-yl). These measurements reveal that the early, sub-picosecond, low-spin to high-spin photoswitching event, with linear response to the laser pulse energy, can be followed under certain conditions by a second switching process occurring on a tens of nanosecond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 44 publications
(14 reference statements)
2
74
1
4
Order By: Relevance
“…In particular, the elastic switching step was shifted by two orders of magnitude toward shorter timescales (20 ns for crystals and 300 ps for nanocrystals) in agreement with the sample size reduction ratio, while the “thermal” step was suppressed due to a more efficient heat transfer with the external environment. Finite size effects have been also observed recently in high quality, thin SCO films revealing a complete suppression of both the thermal and elastic steps in the thinnest films (50 nm) due to the enhanced heat exchange as well as the large temporal decoupling of the lattice expansion from the intramolecular switching phenomenon …”
Section: Emerging Topicsmentioning
confidence: 71%
“…In particular, the elastic switching step was shifted by two orders of magnitude toward shorter timescales (20 ns for crystals and 300 ps for nanocrystals) in agreement with the sample size reduction ratio, while the “thermal” step was suppressed due to a more efficient heat transfer with the external environment. Finite size effects have been also observed recently in high quality, thin SCO films revealing a complete suppression of both the thermal and elastic steps in the thinnest films (50 nm) due to the enhanced heat exchange as well as the large temporal decoupling of the lattice expansion from the intramolecular switching phenomenon …”
Section: Emerging Topicsmentioning
confidence: 71%
“…For our thermal-cycling experiment, the temperature of the wire was modulated between 50 and 88°C by applying 200-µs-long current pulses at a frequency of 200 Hz. Note that the heating duration (200 µs) was chosen long enough compared to the thermally activated molecular spin-state switching time (a few tens of nanoseconds above room temperature 38 ), ensuring that a full LS-HS-LS thermal switching cycle was completed for each current pulse. At selected times, the excitation frequency was lowered to 0.2 Hz in order to record simultaneously the temporal evolution of the optical reflectivity (λ = 452 nm) on the heated microwire.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the temporal resolution, our thermometer is intrinsically limited by the thermally induced switching dynamics of the SCO molecules. From recent femtosecond optical spectroscopy measurements 38 , we know that the thermally activated spin-state switching in the thin films of 1, governed by the LS ↔ HS intramolecular energy barrier, occurs within a few tens of nanoseconds. This time scale thus defines the intrinsic response time of the film, in terms of optical reflectivity change, to any variation of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have shown that very high‐quality, nanocrystalline films of 1 can be obtained by vacuum thermal evaporation followed by solvent vapor annealing . These films exhibit a well‐reproducible thermal SCO (similar to the bulk material) as well as an ultrafast (≈10 −13 s) light‐induced spin state switching at room temperature . With decreasing film thickness, the transition is slightly shifted to higher temperatures, which we attributed to the stabilization of the LS phase by surface energy and stress .…”
Section: Comparison Of Reported Elastic Moduli Ofmentioning
confidence: 82%